2017
DOI: 10.12688/f1000research.11024.1
|View full text |Cite
|
Sign up to set email alerts
|

The "enemies within": regions of the genome that are inherently difficult to replicate

Abstract: An unusual feature of many eukaryotic genomes is the presence of regions that appear intrinsically difficult to copy during the process of DNA replication. Curiously, the location of these difficult-to-replicate regions is often conserved between species, implying a valuable role in some aspect of genome organization or maintenance. The most prominent class of these regions in mammalian cells is defined as chromosome fragile sites, which acquired their name because of a propensity to form visible gaps/breaks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…The effect is exacerbated when DNA replication is challenged by treating cells with low-dose aphidicolin (Aph, Figure 7C). Similar observations have been reported upon other genetic perturbations increasing endogenous replication stress and bona fide reflect genomic regions where replication is not complete upon entry into mitosis (Bhowmick and Hickson, 2017).…”
Section: Rnf168-deficient Cells Show Defects In Replicating Repetitivsupporting
confidence: 83%
“…The effect is exacerbated when DNA replication is challenged by treating cells with low-dose aphidicolin (Aph, Figure 7C). Similar observations have been reported upon other genetic perturbations increasing endogenous replication stress and bona fide reflect genomic regions where replication is not complete upon entry into mitosis (Bhowmick and Hickson, 2017).…”
Section: Rnf168-deficient Cells Show Defects In Replicating Repetitivsupporting
confidence: 83%
“…Although there is a low frequency of complex rearrangement initially associated with chromosome bridges in the first interphase after the bridge has formed, we hypothesized that additional DNA damage might arise downstream of bridge breakage. First, chromosome bridges contain segments of incomplete DNA replication and probably stalled replication forks that could undergo replication fork breakage upon entry into mitosis (51, 52). Second, we found that complex rearrangements were frequent in the second generation (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, one intact daughter chromosome is immediately restored by gap filling, and the other is regenerated via joining of the two broken ends, albeit with sister chromatid exchange and at the cost of of a small deletion (Figure S7, left branch). Importantly, this mechanism avoids the formation of acentric and dicentric chromosomes that would result from random breakage of the forks (Figure S7, right branch) and thus helps account for the fact that breakage at CFS is mostly beneficial (Bhowmick and Hickson, 2017; Minocherhomji et al, 2015; Naim et al, 2013; Ying et al, 2013). Strikingly, CFS expression induces chromosomal alterations that exhibit key features expected of our model, including submicroscopic deletions covering the CFS locus, microhomologies at the breakpoint junctions, and a very high frequency of sister chromatid exchanges (Glover et al, 2017) (Figure S7, left branch).…”
Section: Discussionmentioning
confidence: 99%